Intra-molecular pathways of allosteric control in Hsp70s - Mayer, Matthias P. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2018)
The 70 kDa heat-shock protein (Hsp70) is undoubtedly the most versatile of all molecular chaperones. Hsp70 is involved in numerous cellular protein folding processes, accompanying proteins throughout their lifespan from de novo folding at the ribosome to degradation at the proteasome, surveilling protein stability and functionality. Several properties of this ATP-dependent chaperone constitute the molecular basis for this versatility. With its substrate binding domain (SBD), Hsp70 transiently interacts with a short degenerative linear sequence motif found practically in all proteins and, in addition, with more folded protein conformers. Binding to polypeptides is tightly regulated by ATP binding and hydrolysis in the nucleotide binding domain, which is coupled to the SBD by an intricate allosteric mechanism. Hsp70 is regulated by a host of J-cochaperones, which act as targeting factors by regulating the ATPase activity of Hsp70 in synergism with the substrates themselves, and by several families of nucleotide exchange factors. In this review, I focus on the allosteric mechanism, which allows Hsp70s to interact with substrates with ultrahigh affinity through a non-equilibrium mode of action and summarize what mutagenesis and structural studies have taught us about the pathways and mechanics of interdomain communication.This article is part of a discussion meeting issue ‘Allostery and molecular machines’.
Gesehen am 23.03.2020